Photos of Old Watkins Family Photographs - Watkins, Howard::::::::: (1988)
Aaron "Jack" Watkins, Alma Watkins, Florence Watkins, and Rena Mae Watkins with covered wagons in Phoenix, AZ 1913 Different scratches on photo